Information Analysis Support for Decision-Making in Scientific and Technological Development - Boris Onykiy; Evgeniy Antonov; Alexey Artamonov; Evgeny Tretyakov (International Journal of Technology, 2020)
This paper presents the development of an information and analytical system to foster scientific and technological development in a given scientific field. In this work, the main software tools for implementing distributed computing, which involves a set of software components for collecting, processing, and analyzing large amounts of data, are considered. In addition, various approaches for task coordination between different sets of software are discussed and techniques for storing large amounts of data are described. The system architecture and database schema are designed and tested. Nowadays, the intellectualization of individual software agents is a key aspect of a new generation of multiagent systems. For this reason, this paper develops an approach that can organize activities of a large number of software agents to increase system intellectualization through swarm intelligence at the level of individual agents. Three remote servers were used to build and test the system deployment, comprising such components as a platform for monitoring and scheduling workflow, data storage, and a graphical user interface that enables data retrieval and interaction on the Internet.